Linear complex permittivity of isotropic polar fluids. (October 2019) - Déjardin, Pierre-Michel; Cornaton, Yann
Abstract: An analytical formula for the linear complex permittivity of polar fluids is obtained from the averaged Dean-Kawasaki equation as a function of temperature, density and molecular dipole moment. The static results compare reasonably well with experimental data of some simple polar fluids in their liquid phase, while when the Kirkwood correlation factor is larger than unity, a thermally activated relaxation process appears in the dynamic response.